A novel approach in root coverage - Coronally repositioned flap with GTR membrane and frenotomy - Patil, Veena Ashok (Medknow Publications & Media Pvt Ltd, 2013)
This case report describes a guided tissue regeneration (GTR) based root coverage procedure over maxillary central incisor using coronally advanced flap with simultaneously performed frenotomy. The patient was a 32-year-old female with chief complaint of gingival enlargement in relation to 11. Based on overall findings it was diagnosed as a case of inflammatory gingival enlargement. Vertical osseous defect along with Millers class I gingival recession was seen after initial therapy. GTR-based root coverage procedure using coronally advanced flap with simultaneously performed frenotomy was planned. Complete root coverage was achieved over the maxillary central incisor that initially presented with Miller's class I gingival recession along with radiographic bone fill of the osseous defect. This case report shows the possibility of applying GTR-based root coverage procedure using coronally advanced flap combined with frenotomy to treat Millers class I gingival recession